(untitled) (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity aims to increase the activeness and strengthen the faith formation of SEKAMI children at St. Hendrikus Homa Station, who have so far shown limited involvement in church activities. The low participation of children is influenced by the lack of varied coaching methods and mentoring adapted to the developmental needs of children. Therefore, this program applies an animated approach that emphasizes the role of animators and animatrists in the faith mentoring process. The method used in this activity combines community education and direct mentoring approaches. The program was implemented in several stages, including movement and song animations, Scripture catechesis through storytelling and dialogue, and the introduction of liturgical instruments and vestments. Evaluation was conducted through oral questioning before and after the activities, as well as observation of children’s participation, confidence, and attitudes during the sessions. The results indicate an improvement in children’s participation and understanding of faith materials, as reflected in their involvement in discussions, question-and-answer sessions, and their ability to recall Scripture messages and identify the pillars of SEKAMI and basic liturgical elements. Positive changes were also observed in attitudes such as discipline, cooperation, and respect during prayer and liturgical activities. However, these improvements are still described in a general manner and are not yet supported by more specific and measurable indicators. Therefore, claims regarding the effectiveness of the animated approach should be interpreted cautiously. Nevertheless, the activity demonstrates that creative and sustainable mentoring has the potential to support the faith growth and active participation of SEKAMI children, especially in station communities with limited pastoral assistance.